Comparative study of design methods of design methods of flexible pavement around Shah Alam / Muhyi Ali - Ali, Muhyi (1988)
The thickness of flexible pavement depends mainly upon the strength of the subgrade soil, the strength of the pavement material and the amount of traffic will use the road. In this project the strength of the road subgrades is assessed in terms of the California Bearing Ratio and the pressure sustained per unit deformation of the subgrade soil and these are dependent on the type of soill, it's density and it's moisture content.